Pengaruh Kompetensi Individu dan Lingkungan Kerja terhadap Evaluasi Kinerja Pegawai pada Instansi Pemerintah Daerah - Fahrel Alfais. A; Herlina; Suharno (Jurnal Riset Multidisiplin Edukasi, 2025)
This empirical study examines the impact of individual competence and work environment on employee performance evaluation within a local government agency in Indonesia. Individual competence encompasses knowledge, skills, and professional attitudes, serving as foundational capital in bureaucratic task completion. The work environment includes physical aspects (facilities, ergonomics, and workplace climate) and psychosocial dimensions (interpersonal relationships, leadership style, and organizational culture) that influence employee motivation and productivity. Data were collected via a closed-ended Likert-scale questionnaire from 100 purposively sampled civil servants, then analyzed using multiple linear regression following validity, reliability, and classical assumption tests. Findings reveal that individual competence (β = 0.45, p < 0.001) and work environment (β = 0.38, p < 0.001) significantly positively affect employee performance evaluation, with a coefficient of determination (R²) of 0.62. These results suggest that enhancing training programs to strengthen employee competence and improving facilities and workplace climate are priority strategies for boosting bureaucratic performance.